The Role of Community Engagement in Enhancing Brand Equity Through Brand Trust: A Study of Barudak Kalunar - Dilla Fairuz (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the role of community engagement in enhancing brand equity through brand trust within the Barudak Kalunar community. The research investigates how participation, interaction, and emotional value influence community engagement, how engagement enhances brand trust, and the strategic implications of brand trust in strengthening brand equity. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 200 active members of the Barudak Kalunar community using structured questionnaires with Likert-scale measurements. The results indicate that participation and emotional value significantly influence community engagement, while interaction does not show a significant effect. Furthermore, community engagement significantly enhances brand trust, and brand trust plays a critical role in strengthening brand equity. These findings highlight that emotional attachment and active participation are more influential than communication frequency in building meaningful engagement and trust. The study provides strategic implications for community-based branding by emphasizing systematic trust-building mechanisms as a pathway toward sustainable brand equity development.